Kajian Kerusakan Ekosistem Hutan Mangrove di Kecamatan Kei Besar Kabupaten Maluku Tenggara - Ruban, Engelberta; Sumilat, Grystin Djein; Lobja, Xaverius Erick; Rifani, Irfan (Jurnal Social Science, 2024)
The purpose of this study was to determine the level of damage to mangrove forests, the causes of damage to mangrove forests, and to find out how the role of the government and society in maintaining and preserving mangrove forests in Kei Besar District, Southeast Maluku Regency. The results showed that the damaged condition of the mangrove forest ecosystem, specifically in Kei Besar sub-district, was already in a critical condition (damaged), where most of the mangrove trees were dead/dry due to frequent felling, resulting in a decrease in numbers. This factor is caused by the low awareness of the people who use mangroves as firewood and ignore the function of mangroves as ecosystems that support the coastal environment and fish shelters and fishing grounds must be far from the coast. The role of the government is considered low and there are no rules in the use and preservation of mangroves in Kei Besar District, Southeast Maluku Regency. Therefore, public awareness and even the role of the sub-district government is needed in dealing with the damage to the mangrove forest ecosystem in Kei Besar on an ongoing basis.